Ductile and dry exterior joints using CFRP bolts for moment-resisting frames - Ngo, Tang Tuan; Pham, Thong; Hao, Hong (ELSEVIER SCIENCE INC, 2020)
This study proposes a new dry joint type for moment-resisting frames by using carbon fibre reinforced polymer (CFRP) bolts and plates. This is one of very rare studies focusing on the potential of using CFRP bolts to connect the precast beam-column joints. CFRP bolts have been recognized for their good performances, which could effectively resolve a very costly issue of corrosion in the common dry joints using steel bolts, plates, and tendons. Cyclic loading was applied to test four specimens until 85% of the post-peak load. The results indicated that the proposed dry joints showed better performances compared to the reference monolithic joint in the load-carrying capacity, energy dissipation, and stiffness, which increased by 27–61%, 45–75%, and 27–55%, respectively. Particularly, drift ratio of all the proposed joints exceeded 3%, which is higher than the requirements for ductile joints in various standards. The ductility of the proposed joints was also more preferable than the reference monolithic joint (i.e. 2.2 vs 2.4). These exciting results suggest that these new dry joints can be plausibly applied to prefabricated constructions in non-seismic and seismic-prone areas. In addition, the proposed dry joints offer numerous advantages, compared to the traditional monolithic joints, in terms of construction time and construction-quality control.